Differences in Self-Esteem, Marital Satisfaction, and Social Support of Mothers Raising One Child of Infants by Subsequent Childbirth Plans - Sanglim Kim (International Journal of Advanced Culture Technology(IJACT), 2025)
The purpose of the study was to examine the differences in self-esteem, marital satisfaction, and social support of mothers raising one child of infants by their subsequent childbirth plans. The data from first wave (2022) of the Korean Early Childhood Education and Care Panel Study were used, and the study subjects were 1,371 mothers who were raising one child of infants. The survey questionnaires were used to measure the major variables: Subsequent childbirth plans, self-esteem, marital satisfaction, and social support. The descriptive statistical analysis and analysis of variances were conducted. The results showed that mothers with subsequent childbirth plans reported statistically significantly higher levels of self-esteem, marital satisfaction, and social support compared to those without such plans. Based on the results, I suggested some policies and interventions aimed at enhancing mothers’ psychological well-being, marital relationships, and social support networks.